The Use of Research in Schools: Principals' Capacity and Contributions - Elizabeth N. Farley-Ripple (MDPI AG, 2024)
Policy expectations for the role of research evidence in educational decision-making have grown exponentially in the U.S. and globally, yet there has been limited attention to school capacity to engage in evidence-informed improvement. In this paper, I address this gap by first conceptualizing principal leadership for evidence use and, second, use this conceptual lens to examine large-scale survey data about school evidence use practices and capacity. Drawing on data from a national survey of more than 4000 educators in 134 schools in the US, I explore school practices and capacity to use research and surface opportunities and needs for principal leadership in evidence-informed improvement. Findings suggest that there is an opportunity to improve the role of research in school improvement decision-making, and that principals may contribute to school capacity in specific ways that relate to developing human capital, influencing culture, leveraging resources, and shaping decision-making. Data reveal moderate evidence of research use in agenda setting and of organizational routines that support research use, but lack of uptake of those routines for research use as well as limited investment in resources (e.g., time). Further, decision-making was distributed across a wide range of improvement initiatives, with evidence of a lack of clarity about goals. Although principals report confidence and experience with using research, overall school staff also reported limited experience with prior research, including coursework or participation in research, and low confidence in critically consuming research. Implications point to the need to strengthen principals' own evidence use capacity as well as focus on dimensions school capacity as part of evidence use initiatives. Recommendations suggest strategies for developing principals' knowledge and skills around leadership for evidence-informed improvement.